Phosphorus Recovery and Bioavailability from Chemical Extraction of Municipal Wastewater Treatment’s Waste Activated Sludge: A Case of Bangkok Metropolis, Thailand - Khaing K.T. (2023)
This study evaluated the extractability and bioavailability of Phosphorus (P) recovered from waste activated sludge (WAS) so as to reduce dependence on the import of non-renewable P resources. P extraction was carried out using sulfuric acid (H2SO4). A response surface methodology was used to optimize conditions for the chemical leaching of WAS. The results showed the optimum condition for leaching WAS with 0.1 mol/L H2SO4 for 30 min, resulting in 97% P released. The efficiency of P recovery by P precipitation was associated with pH value and Mg:P. At pH 7, 9, and 11, P recovery was 92, 92, and 91% with uncontrolled Mg and 93, 93, and 92% with sea salt (Mg:P, 2:1), respectively. However, the yield of the produced struvite was much lower compared with that of added sea salt. From elemental analysis, the yield of struvite precipitated at pH 9 of Mg:P, 2:1 was about 26%, and the total P content of the precipitate was 12%. Available P was almost 80% after 35 days of operation, which was higher than that of commercial fertilizers. Results of this study are expected to provide fully comprehensive information to decision-makers regarding the suitability of implementing P-composite matter recovered from WAS. This will also help close the loop of the P cycle for food cultivation in the human ecosystem.